If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 15 = -6 Reorder the terms: 15 + 7x = -6 Solving 15 + 7x = -6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + 7x = -6 + -15 Combine like terms: 15 + -15 = 0 0 + 7x = -6 + -15 7x = -6 + -15 Combine like terms: -6 + -15 = -21 7x = -21 Divide each side by '7'. x = -3 Simplifying x = -3
| 10x-12+10=18+20 | | 3x+5+2x=100 | | y+32=13 | | 5t-7=11-t | | 8+17=9 | | -7x-12=44 | | x^2-3x=-0.5 | | 72+13= | | 3[3(4x-7)-4(2x-7)]=11x+25 | | 3s+5p=tp-5 | | 5[4+6(4x-2)]=6x-838 | | x^2-3x+2.25=1.75 | | 9+8y-4=9y+53-7y | | 6x-10x-5=7 | | 11+5x=-34 | | -8x=8 | | -3(4+x)=-6 | | 3x-(-2)=17 | | 12x-3+10=5(1+3x)-(3+2x) | | 15=2m | | -5+x=7 | | -2+5=19 | | 32x^4-4x^2-1=0 | | x-(-10)=-14 | | -10(12-a)=4(a+3) | | 4x+673(45)=37 | | x+(-8)=-12 | | -8+4b=-8(-4b-6) | | 70=(61+71+70+x)/4 | | 70=(61+71+70+x)/2 | | r(z^8+2)+(z^8+2)=0 | | -7+5v=-5(v-5)+6v |